1973
DOI: 10.1128/aac.4.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of Vancomycin-Gentamicin and Vancomycin-Streptomycin Against Enterococci

Abstract: The in vitro activity of vancomycin and combinations of vancomycin-gentamicin and vancomycin-streptomycin against enterococci was investigated. The minimal inhibitory concentration of vancomycin for 99 of 100 enterococcal strains isolated clinically was 3.12 ,ug or less/ml. When cultures of eight strains were incubated with vancomycin, regardless of the inoculum size (106, 105, or 104) and concentration of vancomycin (10 or 20 qg/ml), there was no significant reduction in the number of viable enterococci at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
29
0
1

Year Published

1975
1975
2004
2004

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(33 citation statements)
references
References 20 publications
(24 reference statements)
3
29
0
1
Order By: Relevance
“…Other investigators have demonstrated this in vitro bactericidal action of daptomycin against various strains of enterococci (4-6, 19, 20). However, in 100% rabbit serum the MBC increased at least sevenfold for daptomycin, and no bactericidal activity was present in time-kill studies by 24 h. Adding gentamicin to daptomycin, penicillin G procaine, or vancomycin led to (2,22). In serum, similar bactericidal activity occurred, but daptomycin-gentamicin was less rapidly bactericidal than penicillin G procaine-gentamicin, vancomycin-gentamicin, or daptomycin-gentamicin in broth.…”
Section: Discussionmentioning
confidence: 70%
“…Other investigators have demonstrated this in vitro bactericidal action of daptomycin against various strains of enterococci (4-6, 19, 20). However, in 100% rabbit serum the MBC increased at least sevenfold for daptomycin, and no bactericidal activity was present in time-kill studies by 24 h. Adding gentamicin to daptomycin, penicillin G procaine, or vancomycin led to (2,22). In serum, similar bactericidal activity occurred, but daptomycin-gentamicin was less rapidly bactericidal than penicillin G procaine-gentamicin, vancomycin-gentamicin, or daptomycin-gentamicin in broth.…”
Section: Discussionmentioning
confidence: 70%
“…As with penicillin and vancomycin, N-formimidoyl thienamycin is not bactericidal against enterococci. Also similar to penicillin and vancomycin (6,7), synergism of Nformimidoyl thienamycin with gentamicin and N-formimidoyl thienamycin with tobramycin was demonstrated against almost all strains tested. Both combinations failed to show synergism against one strain of Streptococcusfaecalis.…”
mentioning
confidence: 87%
“…To cast further doubt on the bacteriologic identification, all of the enterococci were said to be susceptible to cephalothin and one to clindamycin, unusual properties for enterococci (79). In vitro, vancomycin is usually not bactericidal, and it does no better in animal models than penicillin alone (27,99,104,135,205,217). Among other agents that have been evaluated, ciprofloxacin was less effective than procaine penicillin in controlling enterococcal endocarditis (75,104,195).…”
Section: Management Of Enterococcal Infections Therapymentioning
confidence: 99%